2003
DOI: 10.1088/0022-3727/37/2/008
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of ions and neutral active states in the afterglow and their influence on the memory effect in nitrogen at low pressures

Abstract: The influence of positive ions and neutral active states on the memory effect in nitrogen-filled discharge tubes at 1.3 and 4.0 mbar pressures has been investigated. Analysing the thermal velocity of these particles as well as drift velocity of positive ions, it is shown that the positive ions have a dominant role in the breakdown initiation for afterglow periods lower than 30 ms, while the role of the neutral active states can be ignored because of their electrical neutrality. The estimated value of the posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 72 publications
2
22
0
Order By: Relevance
“…21) Because the concentration of those particles is considerable, their mutual collision leads to the formation of positive ions. The calculated value of positive ions drift velocity 22) for the applied voltage of U w ¼ 310 V is about 10 6 cm/s and it is two orders of magnitude higher then their thermal velocity. This means that t d depends on ion drift toward the cathode, electron acceleration toward the anode and electron multiplication.…”
mentioning
confidence: 85%
“…21) Because the concentration of those particles is considerable, their mutual collision leads to the formation of positive ions. The calculated value of positive ions drift velocity 22) for the applied voltage of U w ¼ 310 V is about 10 6 cm/s and it is two orders of magnitude higher then their thermal velocity. This means that t d depends on ion drift toward the cathode, electron acceleration toward the anode and electron multiplication.…”
mentioning
confidence: 85%
“…in the plateau and in the region of sudden increase in t d values. Previous experimental data in nitrogen [16,17] have shown that the memory curve consists of three regions: (1) the plateau region (t d insignificantly depends on τ ), (2) the region of sudden rise in t d with the increase in τ , as can be seen in figures 1 and 2, and (3) the saturation region when t d changes insignificantly. It has been concluded that this behaviour of the memory curve is a consequence of different mechanisms which predominantly influence the SEE process.…”
Section: Resultsmentioning
confidence: 80%
“…Because the energies of some neutral active particles in nitrogen are higher than the cathode material work function, they can release secondary electrons in collision with the metal cathode. The secondary electron emission from the cathode (the SEE process) due to the bombardment of the cathode surface with positive ions and N( 4 S) atoms has an important role in the initiation of breakdown in nitrogen-filled tubes at low pressures, which can be monitored by the time delay method [16,17]. The method consists of acquiring the t d = f (τ ) dependence, also called the memory curve, where t d is the mean value of total time delays t d , i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of neutral active particles in causing the process of secondary electron emission is much smaller than in the case of positive ions, causing the value of t d rapidly increased in relation to the plateau memory curve. Earlier investigations [1], [3], [24], [30] confirmed that the nitrogen atoms in ground state N( 4S) remaining from the previous discharge as well as formed after the discharge ceased are the most responsible particle for the secondary electron emission from the cathode in late nitrogen afterglow. Numerical models, which followed the decrease of nitrogen atoms concentration based on the re-association on the tube walls [3], [4], [24] combined with a model predicts that secondary electron emission is caused by nitrogen atoms, showed a good agreement with the experimental obtained memory curves in the area of sudden increase in t d value.…”
Section: Nitrogen Memory Effectmentioning
confidence: 96%